KAJIAN CARA BERHUBUNGAN BADAN YANG BENAR DALAM NASKAH RISALAH - Ridwan Ridwan (Jurnal Akrab Juara, 2019)
This study examines Malay manuscripts about how to deal with good bodies so as to produce good and bad results with results that humiliate and humiliate the body in the treatise text written in Malay Arabic script. Descriptive qualitative analysis research method that begins the process of transliteration from the Jawi script to the Latin script as well as relevant studies related to this text, this study is very important to be explored more deeply, because mistakes in intercourse will result in various diseases such as HIV, back pain, weakness knees, gray hair and ugly faces in children, and lack of common sense and foolishness, it is very important to inform the general public that they can benefit.